Mediation Role of External Locus of Control on the Influence of Financial Attitude and Financial Knowledge on Financial Management Behavior - Mentari Clara Dewanti; Daisy Martina Rosyanti; Fani Khoirotunnisa (Budapest International Research and Critics University, 2022)
This study aims to determine how the external locus of control mediates the influence of financial attitudes and financial knowledge on financial management behavior. Data was collected using a questionnaire distributed online to students majoring in management belonging to class Z UPN